China-Nepal Think Tank Cooperation: Significance, Status and Prospects - Yang, Weifeng (Khwopa Journal, 2024)
Think tanks play an important role in the friendly relationship between China and Nepal. China-Nepal think tank exchanges and cooperation is the proper meaning of building a China-Nepal destiny community, fits the inherent objectives of China-Nepal think tank construction, and can provide effective intellectual support for the construction of the “Belt and Road” together with China and Nepal. At present, China-Nepal think tank cooperation has made remarkable progress: the two countries have set up specialized China study and Nepal study institutes, published a large number of reports, theses, monographs and media commentaries, intensively organized forums and conferences to improve exchange and cooperation mechanisms, promoted public diplomacy of think tanks to reinforce the people-to-people bonds between China and Nepal, and at the same time, they have also joined hands to build an international and interdisciplinary think tank platform with mountain characteristics. In the face of some shortcomings in the existing cooperation, both sides should strengthen the comprehensive capacity building of the two countries’ think tanks, explore emerging topics such as digital and green transformation, promptly bridge the cognitive differences in China-Nepal cooperation, and ensure the objectivity and truthfulness of the information sources and knowledge outputs. Only in this way can China-Nepal think tank cooperation create new paths, expand its influence and enhance its effectiveness, and play a stronger role as an intellectual engine for deepening the development of the China-Nepal relationship.